ANALISIS PENDAPATAN PER KAPITA KABUPATEN BONE BOLANGO - Apris Ara Tilome; Harijono H. Imbran; Inra . (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2021)
Per capita income is a parameter to determine the success of economic activities in a country or region and is usually calculated in one year based on the results of economic activities as reflected by Gross Regional Domestic Product (GRDP). This study aims to analyze the income per capita of the Bone Bolango Regency. This study uses a quantitative approach, and the analysis is on 5-year Gross Regional Domestic Product (2015-2019) time series data. The results show that the economic development of Bone Bolango Regency, which is indicated by the average economic growth is still above 6 percent, and the population growth rate reaches 1.29 percent in the 2015-2019 period. With the fluctuating economic development based on GRDP both based on constant prices and based on current prices, it generates per capita income of Bone Bolango Regency in 2015-2019, namely: a) Per Capita Income Based on Constant Prices is Rp. 1.311.007.54,- per year b) Income Per Capita Based on the Current Price is Rp. 1,836,215.54, - per year. Keywords: Local Tax, Economic growth